Essays on the economic consequences of information asymmetry and accounting conservatism in the mergers and acquisitions market - Elgendi, Hassan Yassin Hassan (2020)
Merger and acquisition (M&A) transactions arguably represent one of the most significant events that firms might experience over their lifecycles; yet many transactions are value-neutral or value-destroying for shareholders of acquiring firms. Throughout three empirical essays, this thesis explores the economic consequences of two aspects of information uncertainty of the target firm (the seller) on acquisition decisions of the acquiring firm (the buyer) and outcomes of M&A transactions. First, this thesis investigates whether the target’s ex ante information asymmetry benefits the target’s shareholders at the expense of the acquirer’s shareholders, and whether it affects the M&A deal termination and renegotiation decisions, as well as the acquirer’s long-term performance. The results show that while a target’s information asymmetry is beneficial for shareholders of target firms by increasing takeover premiums they receive and positive abnormal stock returns they achieve upon the announcement of M&A deals, it negatively affects shareholder wealth of acquiring firms. The results also reveal that deals involving target firms with high information asymmetry are more likely to be terminated or renegotiated. Furthermore, the results show that the acquirer is more likely to post-acquisition report goodwill impairment losses when the target firm has high information asymmetry, indicating that the target’s information asymmetry negatively influences the acquirer’s long-term performance. Next, this thesis explores the link between conservative accounting of the target firm and the takeover premium. It also examines the moderating effect of the target’s ex ante information asymmetry on this link. The results show that the winning acquirer incurs a lower premium when the financial reporting of the target firm is more conservative over the years preceding the acquisition, suggesting that the target’s conservative accounting helps the acquirer to bid more effectively in the M&A market by avoiding the potential overpayment to target shareholders. Moreover, the results show that the role of the target’s conservative accounting in decreasing the possibility of the acquirer’s overpayment is more prominent when the target firm has high ex ante information asymmetry. Finally, this thesis examines whether conservative accounting of the target firm is associated with shareholder wealth of both the target and acquiring firms, as reflected by the stock market reaction to the announcement of the M&A deal. The results show that abnormal stock returns for target shareholders around the deal announcement are lower when the financial reporting of the target firm is more conservative. The results also reveal that abnormal returns for shareholders of the winning acquirer are higher when the target’s conservative accounting is high. These results denote that conservative accounting of a target firm mitigates the potential disruption in the wealth transfer from acquirer shareholders to target shareholders in M&A transactions that might arise from the high information uncertainty of target firms. Overall, this thesis suggests that managers of acquiring firms should consider discounting the values of target firms in M&A transactions when target firms have high levels of information uncertainty. This thesis also suggests that a target’s conservative accounting plays a vital role in the efficient capital allocation of economic resources by mitigating the adverse consequences of information asymmetry between merging parties in the M&A market.
Keywords: Accounting